Psychosocial impacts of social isolation due to COVID-19 in children, adolescents and young people: A scoping review - Letícia Camilo Santos; Tayná July Silva Pinheiro; Thayane Ingrid Xavier de Andrade; Paulo Henrique Alves Sousa; Patrícia Pinto Braga; Márcia Christina Caetano Romano (Universidade Federal de Santa Maria, 2021)
Objective: to map the psychosocial impacts caused by social isolation during the COVID-19 pandemic in children, adolescents and young people. Method: a scoping review conducted according to the method proposed by the JBI and adopting the recommendations set forth in the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews international guide. The review protocol was registered in the Open Science Framework. Results: a total of 20 articles comprised this review. Depression (70%; n=14) and anxiety (60%; n=16) were the most frequent symptoms among the research studies evaluated. An increase in screen time and in Internet use was identified. Conclusion: social isolation due to COVID-19 has exerted social and psychological effects on children's and adolescents' lives. In this population, mental ailments and their repercussion in child-youth development cannot be disregarded.